Experimental assessment of phase aberration correction for breast MRgFUS therapy. (18th August 2018) - Dillon, Christopher R.; Farrer, Alexis; McLean, Hailey; Almquist, Scott; Christensen, Douglas; Payne, Allison
Abstract: Purpose: This study validates that phase aberrations in breast magnetic resonance-guided focussed ultrasound (MRgFUS) therapies can be corrected in a clinically relevant time frame to generate more intense, smaller and more spatially accurate foci. Materials and methods: Hybrid angular spectrum (HAS) ultrasound calculations in an magnetic resonance imaging (MRI)-based tissue model, were used to compute phase aberration corrections for improved experimental MRgFUS heating in four heterogeneous breast-mimicking phantoms ( n  = 18 total locations). Magnetic resonance(MR) temperature imaging was used to evaluate the maximum temperature rise, focus volume and focus accuracy for uncorrected and phase aberration-corrected sonications. Thermal simulations assessed the effectiveness of the phase aberration correction implementation. Results: In 13 of 18 locations, the maximum temperature rise increased by an average of 30%, focus volume was reduced by 40% and focus accuracy improved from 4.6 to 3.6 mm. Mixed results were observed in five of the 18 locations, with focus accuracy improving from 6.1 to 2.5 mm and the maximum temperature rise decreasing by 8% and focus volume increasing by 10%. Overall, the study demonstrated significant improvements ( p  < 0.005) in maximum temperature rise, focus volume and focus accuracy. Simulations predicted greater improvements than observed experimentally, suggesting potential for improvement in implementing the technique. The complete phase aberration correction procedure, including model generation, segmentation and phase aberration computations, required less than 45 min per sonication location. Conclusion: The significant improvements demonstrated in this study i.e., focus intensity, size and accuracy from phase aberration correction have the potential to improve the efficacy, time-efficiency and safety of breast MRgFUS therapies.